PENGUATAN TOLERANSI BAGI PEMAJUAN BUDAYA KEAGAMAAN: STUDI ATAS PRAKTIK TOLERANSI AGAMA DI PUJA MANDALA BALI - Muhammad Nur Prabowo Setyabudi (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2020)
Tolerance is acknowledged as the principle of national cultural advancement agenda as it has been planned by the government through The Law No. 5 of 2017. In this matter, the advancement of religious culture encourages the concept of diversity and religious management. This research discusses about how the conception of a more mature tolerance for religious management and the advancement of religious culture in Indonesia. By referring the local wisdom and reflecting the tolerance portraits of the field research in one of the tolerance center in Puja Mandala Bali, this research delivers a description and analysis upon a more ultimate model of tolerance. The writer uses a transformative approach to elaborate the concept of tolerance which emphasizes on the respect of equality between the majority and minority. The conclusion shows that the religious culture projection in the future to establish an excellent tolerance urges to leave a permissive and dominative tolerance and to brace a mutualistic and reciprocal tolerance with mutual relations (mutual-respect and mutual-recognition) as it has been projected by the people in Puja Mandala. This research also emphasizes the significance of the art, philosophy and science for the cultural approach toward interreligious harmony.